2021
DOI: 10.30657/pea.2021.27.30
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance Evaluation of a Pulverizer for Plantain Flour Process Plant

Abstract: Diabetes, adjudged a risk factor for coronavirus infectious disease 2019 (COVID-19), can be managed through consumption of plantain and its associated products. Plantain is usually processed into flour and other storable/value-added products due to its very short shelf-life. To process unripe plantain pulps into flour, there is a need for size reduction after drying. This paper presents the development and performance evaluation of a size reduction unit for pulverizing, sieving and conveying material to the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…1 is a locally fabricated machine made from stainless steel for converting different dried food items such as plantain, cassava, maize etcetera into the production of flour. It consists of the structural base, bottom casing, top casing (pulverizing chamber), transmission shaft, hammers, hammer hangers, screen (particle sieve), transmission bearings, pulleys, toothed V-belt, electric motor (5 hp), inlet hopper, inlet regulatory device, pillow bearings, belt cover, bolts and nuts (Olutomilola et al, 2021). Pulverizing machine comprises one central shaft from which four rigid shafts carrying a series of exchangeable hammers have their attachment and enclosure within a metallic casing.…”
Section: Introductionmentioning
confidence: 99%
“…1 is a locally fabricated machine made from stainless steel for converting different dried food items such as plantain, cassava, maize etcetera into the production of flour. It consists of the structural base, bottom casing, top casing (pulverizing chamber), transmission shaft, hammers, hammer hangers, screen (particle sieve), transmission bearings, pulleys, toothed V-belt, electric motor (5 hp), inlet hopper, inlet regulatory device, pillow bearings, belt cover, bolts and nuts (Olutomilola et al, 2021). Pulverizing machine comprises one central shaft from which four rigid shafts carrying a series of exchangeable hammers have their attachment and enclosure within a metallic casing.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, this study is a significant part of the development of a plantain flour processing plant, which will address the growing market demand for plantain due to the increasing understanding of its nutritional and health benefits and industrial/commercial qualities (Olutomilola et al, 2016(Olutomilola et al, , 2019(Olutomilola et al, , 2020. Plantain is affordable and its products (i.e., flour) was found to be effective for managing diabetesa risk factor for coronavirus infectious disease 2019 and one of the world's five leading causes of death and debilitating diseaseswith no adverse side effects (Oluwajuyitan and Ijarotimi, 2019;Adeyeri et al, 2020;Olutomilola, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that, apart from sun-drying, cabinet drying is the most used method for drying plantain pulps after they have been sliced (Olutomilola, 2019). Thus, some researchers have developed a variety of cabinet dryers with varying capacities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations